LEXICAL COLLOCATION OF POLITICAL NEWS PUBLISHED ON 19 May 2020 – 28 May 2020 IN THE JAKARTA POST - Syaifudin Latif D; Achmad Zaenuri Rais (Journal of English Education and Enterpreneurship (JEEP), 2021)
Collocation is a pair of group that often used together. This research aims to describe the types of lexical collocation of political news in the jakarta post. Lexical collocation is the object of this research. The subject of this research is political news in the Jakarta Post Newspaper published on 19 May – 28 May 2020. It consists of 5 news.The researcher took all of the news about politics published on 19 May 2020 – 28 May 2020. The result of this study found 27 lexical collocations,divided into 7 types of lexical collocation. The most dominantly is L3 adjective + noun type, the percentage shows 14 times or 51,9%, the second one is L5 noun + noun type, the percentage shows 8 times or 29,7 %,next one is L1 verb + noun/ pronoun type, the percentage show 3 times or 11,2%, then L2 verb + noun and L4 noun + verb types found 1 time or 3,8 %, both of them have same percentage. The last L6 adverb + adjective and L7 Verb + adverb type not found lexical collocation in the Jakarta Post Newspaper. Furthermore based on the findings, it can be concluded that type L3 adjective + noun is the dominant or highest percentage than all of the patterns.